Effect of solution molarity on optical properties of Al doped ZnO thin films - Rashid, ARA; Othman, NS; Dasuki, KA (IOP Publishing Ltd, 2024)
Undoped and Al-doped ZnO thin films have been prepared by the sol gel method. Zinc acetate dihydrate, ethanol and monoethanolamine were used as precursor, solvent and stabilizer, respectively. In the case of molarity study for Al-doped ZnO, aluminum nitrate nonahydrate was added to the precursor solution from 0 at. % to 6 at. % at molarity of 0.1 M, 0.2 M and 0.3 M. The optical properties were characterized using UV-Vis where the band gap of undoped ZnO increases as the annealing temperature increase and the band gap decrease as the molarity increment. Meanwhile the band gap increase upon increment of Al dopant under molarity of 0.1 M and 0.2 M due to Burstein-moss effects. Meanwhile at 0.3 M, the bandgap increase until 4 at. % of Al and suddenly decrease abruptly at 6 at. % of Al. The effect of molarity and dopant percentage on the thin film gives a different value of energy band gap.